Sexuality of women with multiple sclerosis - Błażejewska, Anita; Lew-Starowicz, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2009)
Sexual dysfunction is a significant, but unfortunately underestimated symptom of multiple sclerosis. It seems to be obvious that disorder, which produces demyelization lesions all over the white matter of central nervous system, can cause not only sphincteric dysfunction or disability, but also sexual disturbances. The purpose of this article is to describe what these disturbances are in women and how to act with patients with sexual health condition like those.